Warren Buffett invests like a girl and why you should too - Lofton, LouAnn (New York, HarperBusiness, 2011)
"Investing isn?t a man?s world anymore--and this book shows why that?s a good thing for individual portfolios, Wall Street, and the world?s financial system
Includes index
Keywords: Investments -Psychological aspects